The challenges of the housing economy : an international perspective - Jones, Colin, 1949 January 13-; White, Michael, 1965-; Dunse, Neil. (Hoboken, N.J. : Wiley-Blackwell, 2012)
This timely book addresses key challenges faced by policy makers and the house-building industry in a post-credit crunch world. It examines the implications for households, the housing market, the economy, as well as for government's policy choices. Challenges of the Housing Economy: an international perspective brings together experts from around the world to examine recent housing market trends. The contributions reveal common long-term trends in housing markets worldwide. Despite differences in supply conditions and the role of planning, there is a trend toward rising house prices that has.
Contributors -- Glossary -- Introduction : the housing economy and the credit crunch -- The housing boom, the bust and US housing po licy -- Housing bubbles and foreclosures that follow : the case of Las Vegas -- Unemployment risk, homeownership, and housing wealth : lessons from the bubble -- The changing nature of household demand and housing market trends in China -- The structural sustainability of home ownership in Australia -- Impacts on wealth and debt of changes in the Danish financial framework over a housing cycle -- Market stability, housing finance, and home ownership in Germany -- The responsiveness of new supply to house prices : a perspective from the Spanish housing market -- The UK housing market cycle and the role of planning : the policy challenge following the financial crisis -- Developments in the role of social housing in Europe -- Delivering affordable housing in the UK -- The UK private rented sector as a source of affordable accommodation -- Conclusions: the challenges ahead -- References -- Index.
Conference proceedings.
Includes bibliographical references and index.
Print version record.
Keywords: 2008 - 2009; Housing -- Prices -- Congresses; Real estate business -- Congresses; Real property -- Ownership -- Congresses; Global Financial Crisis, 2008-2009 -- Congresses; Housing policy -- Congresses; BUSINESS & ECONOMICS -- Real Estate -- General; Housing policy; Housing -- Prices; Real estate business; Real property -- Ownership; Electronic books; Conference papers and proceedings